HOW INVESTMENT ACTIVITY AND CORPORATE GOVERNANCE AFFECT THE DISCLOSURE OF ESG - Anggraini, Melisa; Darsono, Darsono; Octavio, Danes Quirira (Jurnal Akuntansi dan Keuangan Indonesia, 2025)
Background: This research investigates the impact of corporate governance elements and corporate investment activity on ESG disclosure in companies from Asia Pacific Emerging Markets. Methods: The study analyzes a sample of 150 companies from Asia Pacific Emerging Market countries over the period 2015–2022, yielding a total of 1200 observations. The Generalized Method of Moments-Difference (GMM-DIFF) is employed to test the hypothesis. Four independent variables related to corporate governance and one variable representing investment activity are used. Findings: The results show that investment in property, plant, and equipment assets, as well as the presence of audit committees, positively affect ESG disclosure in these markets. Conclusion: The findings highlight the significance of both asset investment in property, plant, and equipment and the role of audit committees in enhancing ESG disclosure among firms in Asia Pacific Emerging Markets. Novelty/Originality: To the best of our knowledge, this is the first study to examine the influence of property, plant, and equipment asset investment as a determinant of ESG disclosure in Asia Pacific Emerging Countries.